Natural convection heat transfer and fluid flow in a thermal chimney with multiple horizontally-aligned cylinders - Ma, H; He, LI; Yu, G; Yu, Z (Elsevier, 2021)
To address the scarcity of natural convection research for the tube array with three or more columns of horizontallyaligned cylinders, this paper conducts RANS/URANS simulations for multiple cylinder columns in one or two rows, validated by particle-image velocimetry and heat transfer measurements. Parametric study with varying horizontal and vertical pitches is implemented by RANS with transition SST model. Key findings are then substantiated and examined by URANS. It is found that the horizontal pitch influences the balance between the chimney effect and the blockage effect, thus has an optimum with respect to the natural draft velocity. For all the vertical distances computed in the two-row thermal chimney model, the flow pattern stays in a plume-dominant mode at the large horizontal pitch and a chimney-dominant mode at the small horizontal pitch. Interestingly, at the intermediate horizontal pitch (pitch/diameter2.5), the flow pattern switches from plume-dominant to chimney-dominant over a minor increase of the vertical pitch (from 4.5 to 6 diameters), leading to significant augmentation in natural draft velocity and heat transfer on cylinder surfaces. This distinct thermo-flow behavior, identified for the first time to the authors’ knowledge, may be harnessed to improve the performance of passive heat exchangers.